The hydrothermal alkaline alteration of potassium feldspar: A nanometer-scale investigation of the orthoclase interface - Hellmann, Roland; Zhai, Yuanyuan; Robin, Eric; Findling, Nathaniel; Mayanna, Sathish; Wirth, Richard; Schreiber, Anja; Cabié, Martiane; Zeng, Qingdong; Liu, Shanke; Liu, Jianming (Chemical geology, 2021)
Potassium feldspars (KAlSi3O8) are ubiquitous minerals in the Earth's upper crust. This family of minerals has been the subject of numerous experimental and theoretical investigations concerning their dissolution kinetics and the mechanisms controlling chemical alteration at acid and neutral pH, and at temperatures ranging from ambient to hydrothermal conditions. On the other hand, considerably less research on the dissolution behavior of K-feldspars has been carried out at alkaline conditions, in particular at pH > 9 and elevated temperatures. Filling in this gap in knowledge is the major motivation for this study. More specifically, we wanted to document and understand how the K-feldspar interface structurally and chemically evolves during alteration in order to determine the mechanism of dissolution. In this study we examined interfaces of orthoclase samples that were altered in separate experiments in a Ca(OH)2-H2O solution (pH25°C 12.4) at 190 °C for 24 h. We used a combination of focused ion beam (FIB) milling and advanced analytical transmission electron microscopy (TEM) techniques to investigate the structure and chemistry of the near surface region of post-reaction grains, with particular attention being given to the fluid-solid interface. Even though each grain diminishes in volume due to dissolution, high-resolution TEM imaging indicates that the feldspar structure itself remains completely intact and crystalline, as evidenced by lattice fringes that abruptly terminate at the grain edge. Nanometer-scale chemical composition measurements and mapping by TEM-EDXS (energy dispersive X-ray spectroscopy) and EFTEM (energy filtered TEM) show that the chemistry of the parent feldspar also remains unchanged at the interface. In particular, there is no evidence for the incursion of Ca from the fluid solvent into the structure, either by interdiffusion or by a replacement process. Taken together, the TEM observations point to a sharp chemical reaction front characterized by the congruent (i.e. stoichiometric) release of all elements from the feldspar structure. Nanometer-scale measurements by high resolution analytical TEM also reveal that a surface alteration layer (SAL) of amorphous material forms in situ at the expense of the feldspar structure. The interface demarcates a spatially coincident and nm-sharp chemical and structural discontinuity between the parent feldspar and the amorphous phase. The amorphous SAL has a variable thickness, from under 10 nm up to ~200 nm. This is likely one of the first observed occurrences of a significant surface amorphous layer on feldspar due to alteration in an alkaline solvent. The lack of a gap between the two phases points to an interfacial dissolution-reprecipitation process that continuously operates during hydrothermal alteration, and mostly likely right from the onset of contact with the fluid. After the initial formation of the amorphous layer, a 1–2 μm-thick porous amalgam of secondary crystalline phases comprised of calcite, tobermorite, and hydrogrossular, as well as other minor phases, precipitated over the SAL. These authigenic crystalline minerals formed during the experiment (hydrothermal alteration, followed by fluid loss due to evaporation) by a classical thermodynamically-controlled precipitation process as the reactor bulk fluid became increasingly concentrated. We propose that a coupled interfacial dissolution-reprecipitation (CIDR) mechanism best explains the chemical and structural properties of the interface and the formation of an amorphous surface layer. In fact, many recent studies postulate that a CIDR process controls feldspar dissolution and the formation of SALs at acid and circumneutral pH over a wide range of temperatures. Combining these previous results with our new observations supports the idea that a unique and unifying mechanism likely controls chemical alteration of feldspars in all aqueous fluids. EFTEM calcium map of reacted orthoclase grain with authigenic crystalline silicate rind. [Display omitted]